A Quantum Dot-Immunofluorescent Labeling Method to Investigate the Interactions between a Crinivirus and Its Whitefly Vector - Ng, James C. (Frontiers in Microbiology, 2013)
Successful vector-mediated plant virus transmission entails an intricate but poorly understood interplay of interactions among virus, vector, and plant. The complexity of interactions requires continually improving/evaluating tools and methods for investigating the determinants that are central to mediating virus transmission. A recent study using an organic fluorophore (Alexa Fluor)-based immunofluorescent localization assay demonstrated that specific retention of Lettuce infectious yellows virus (LIYV) virions in the anterior foregut or cibarium of its whitefly vector is required for virus transmission. Continuous exposure of organic fluorophore to high excitation light intensity can result in diminished or loss of signals, potentially confounding the identification of important interactions associated with virus transmission. This limitation can be circumvented by incorporation of photostable fluorescent nanocrystals, such as quantum dots (QDs), into the assay. We have developed and evaluated a QD-immunofluorescent labeling method for the in vitro and in situ localization of LIYV virions based on the recognition specificity of streptavidin-conjugated QD605 (S-QD605) for biotin-conjugated anti-LIYV IgG (B-αIgG). IgG biotinylation was verified in a blot overlay assay by probing SDS-PAGE separated B-αIgG with S-QD605. Immunoblot analyses of LIYV using B-αIgG and S-QD605 resulted in a virus detection limit comparable to that of DAS-ELISA. In membrane feeding experiments, QD signals were observed in the anterior foregut or cibarium of virion-fed whitefly vectors but absent in those of virion-fed whitefly non-vectors. Specific virion retention in whitefly vectors corresponded with successful virus transmission. A fluorescence photobleaching assay of viruliferous whiteflies fed B-αIgG and S-QD605 vs. those fed anti-LIYV IgG and Alexa Fluor 488-conjugated IgG revealed that QD signal was stable and deteriorated ∼7 to 8 fold slower than that of Alexa Fluor.